470 Blood-based Brain and Global Biomarker Changes Following Combined Hypoxemia and Hemorrhagic Shock in a Rat Model of Penetrating Ballistic-Like Brain Injury. (1st April 2022) - Pierre, Kevin; Li, Xue; Yang, Zhihui; Nugyen, Lynn; Johnson, Gabrielle; Venetucci, Juliana; Torres, Isabel; Lucke-Wold, Brandon; Shi, Yuan; Boutte, Angela; Shear, Deborah; Leung, Lai Yee; et al.
Abstract : INTRODUCTION: Penetrating traumatic brain injury (pTBI) often occurs with systemic insults like hemorrhagic (HS) and hypoxemic (HX) shock. METHODS: 30 rats were randomly assigned to sham, PBBI, HS+HX, and PBBI+HS+HX groups. PBBI and sham groups underwent craniotomy with and without probe insertion and balloon expansion, respectively. HX and HS was then simulated by blood withdrawal and FiO2 reduction. Biomarker serum concentrations were determined at one (D1) and two (D2) days post-injury with ELISA methods. RESULTS: Axonal injury-linked biomarkers pNF-H and NF-L serum levels in PBBI groups were higher than those in sham and HX + HS groups at D1 and D2 post-injury. The same was true for PBBI + HX + HS compared to sham (D2 only for pNF-H) and HX + HS groups. However, pNF-H and NF-L levels in PBBI + HX + HS were not different than their PBBI counterparts. At D1, αII-spectrin levels in the HX + HS and PBBI + HS + HX groups were higher than the sham groups. αII-spectrin levels in the HX + HS group were higher than the PBBI group. This suggests HX + HS as the common insult driving αII-spectrin elevations. CONCLUSION: pNF-H and NF-L may serve as specific serum biomarkers of penetrating TBI in the presence or absence of systemic insults. αII-spectrin may be a sensitive acute biomarker in detecting systemic insults occurring alone or with pTBI.